PENGARUH LABA DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN - Purna Anggara, I Wayan Gde Wahyu; Dwirandra, A. A. N. B (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.08.TAHUN 2020DO - 10.24843/EEB.2020.v09.i08.p04, 2020)
This study uses Lintner's (1956) dividend estimation model to test the effect of earnings and leverage on dividend policy. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange between 2014 to 2016. Sampling research conducted by purposive sampling technique which further collected as many as 52 company samples with 139 observations. This study meets the pre-assumption test required as a requirement to perform multiple linear regression analysis. The results of the analysis show that: (1) earnings has a positive effect on dividend policy, (2) leverage has no negative affect on dividend policy.